Correlates of behavioral and emotional disorders among school-going adolescents in Uganda. - Max Bobholz; Julia Dickson-Gomez; Catherine Abbo; Arthur Kiconco; Abdul R Shour; Simon Kasasa; Laura D Cassidy; Ronald Anguzu (PLOS Global Public Health)
Background Adolescence is a critical development transition period that increases vulnerability to poor mental health outcomes. Recent evidence suggests that adolescents in Uganda experience high rates of behavioral and emotional disorders. We examined the factors associated with emotional and behavioral health outcomes among school-going adolescents in Uganda. Methods In this cross-sectional study, we surveyed 1,953 students aged 10-18 enrolled in Central and Eastern Uganda secondary schools selected by stratified random sampling. Our outcome variables were (i) emotional and (ii) behavioral disorders that were measured using the Child and Adolescent Symptom Inventory-5 (CASI-5) diagnostic criteria outlined in the Diagnostic Statistical Manual-5 (DSM-5). Emotional disorders included major depressive disorder, generalized anxiety disorder, social anxiety disorder, and separation anxiety disorder. Attention deficit/hyperactivity disorder, conduct disorder, and oppositional defiant disorder were considered behavioral disorders. Covariates included socio-demographic, hardship-related experiences, and school-related characteristics. Modified Poisson and logistic regression models were appropriately run for the factors independently associated with respective outcomes. Prevalence ratios (PR), odds ratios (OR), and corresponding 95% confidence intervals (95%CI) were reported with p < 0.05 considered significant. Results Participants' mean age was 15.5 (SD = 2.0) years; 54.7% were female, 5.7% had a behavioral disorder, and 17.4% had an emotional disorder. In the adjusted models, factors independently associated with higher odds of behavioral disorder were age (OR=1.2; 95%CI 1.1 - 1.4) and family history of mental illness (OR=1.9; 95%CI 1.2 - 3.3). Factors independently associated with a higher risk of emotional disorder were being female (PR = 1.5; 95%CI 1.2 - 1.8), being enrolled in advanced education (PR = 1.7; 95%CI 1.2 - 2.4) and attending private school (PR = 1.4; 95%CI 1.1 - 1.8). Conclusions Behavioral and emotional disorders are prevalent among adolescents enrolled in secondary schools in Central and Eastern Uganda. Investigating potential causal pathways of the identified associations is critical to support school mental health initiatives. School-based programs should enhance routine mental health assessments and target at-risk students in order to improve the mental health of school-going adolescents in Uganda.